2023
DOI: 10.3390/su151813695
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Energy Dissipation in T-Shaped Fractured Rocks under Different Loading Rates

Yong Zhang,
Lijia Zhong,
Fan Pang
et al.

Abstract: T-shaped fractured rocks in the engineering rock mass with different inclination angles, quantities, and cross patterns will cause slope landslides, cavern collapse, roof fall, and other disasters under the action of external forces. Deformation evolution of the T-shaped fractured rock is also significant for monitoring the stability of rock engineering structures. In this paper, the compression test of T-shaped fracture specimens was carried out under different loading rates. By modulating both the fracture i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In thermodynamics, any equilibrium state can be characterized either as a state of maximum entropy for a given energy or as a state of minimum energy for a given entropy [30]. In structural mechanics, the strain energy and the principle of minimum total potential energy exist in many applications [31][32][33][34][35][36][37][38][39][40], but the principle of maximum entropy is not commonly considered. Equation ( 22) establishes a link between structural mechanics and thermodynamics.…”
Section: Entropy and Virtual Temperaturementioning
confidence: 99%
“…In thermodynamics, any equilibrium state can be characterized either as a state of maximum entropy for a given energy or as a state of minimum energy for a given entropy [30]. In structural mechanics, the strain energy and the principle of minimum total potential energy exist in many applications [31][32][33][34][35][36][37][38][39][40], but the principle of maximum entropy is not commonly considered. Equation ( 22) establishes a link between structural mechanics and thermodynamics.…”
Section: Entropy and Virtual Temperaturementioning
confidence: 99%
“…From the numerical simulation results, it can be seen that the loadbearing performance and energy absorption of the U-shaped steel support with a uniform load are better than those of the U-shaped steel support with a centralized load. Yong Zhang [9] et al studied the Characteristics of Energy Dissipation in T-Shaped Fractured Rocks under Different Loading Rates. It is found that with the increase in loading rate, the total absorbed energy and elastic energy at the peak point of the T-fractured rock specimen increase, but the dissipated energy decreases.…”
Section: Introductionmentioning
confidence: 99%